2021
DOI: 10.3390/electronics10172088
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient On-Demand Hardware Replacement Platform for Metamorphic Functional Processing in Edge-Centric IoT Applications

Abstract: The paradigm of Internet-of-things (IoT) systems is changing from a cloud-based system to an edge-based system. These changes were able to solve the delay caused by the rapid concentration of data in the communication network, the delay caused by the lack of server computing capacity, and the security issues that occur in the data communication process. However, edge-based IoT systems performance was insufficient to process large numbers of data due to limited power supply, fixed hardware functions, and limite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…We conducted research on the real-time hardware reconfiguration of edge devices [18,19]. This real-time hardware reconfiguration research showed that the execution flow of an application can be predicted and that the hardware to be executed next to the edge device can be reconfigured in advance [20,21]. This process changes the service in real time by partially modifying the firmware of the edge device [22,23].…”
Section: Related Workmentioning
confidence: 99%
“…We conducted research on the real-time hardware reconfiguration of edge devices [18,19]. This real-time hardware reconfiguration research showed that the execution flow of an application can be predicted and that the hardware to be executed next to the edge device can be reconfigured in advance [20,21]. This process changes the service in real time by partially modifying the firmware of the edge device [22,23].…”
Section: Related Workmentioning
confidence: 99%
“…The smart home is equipped with event-driven IoT sensors which are directly connected to the main edge device. The main edge device is loaded with a pre-trained model used for human activity classification and is connected to a high-performance server [32]. Step 2…”
Section: Smart Home Modelmentioning
confidence: 99%
“…In our previous work, we proposed a prototype of a partial firmware replacement for a run-time network model [21][22][23][24][25]. This technique involves selecting a model corresponding to the input data domain from a memory-limited device.…”
Section: Related Workmentioning
confidence: 99%